2014
DOI: 10.1111/ffe.12182
|View full text |Cite
|
Sign up to set email alerts
|

Impact response of polyethylene sandwich panel obtained by rotational moulding

Abstract: A B S T R A C T Sandwich panels are more and more used in load bearing structures because of their high specific stiffness and high specific strength. Impact energy absorption is a characteristic required for some specific application, that is, in high-speed transportations. In this article, the impact response of a new sandwich panel made up of two polyethylene skins separated by lightweight polyethylene foam, built with an innovative manufacturing process called rotational moulding, is investigated by both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Casavola et al [22] studied the low impact behavior of three-layer materials produced by rotational molding made from two polyethylene layers enclosing a foam layer. The results showed that the average force to penetrate the external face was about 28% higher compared to the internal face, which is related to the compression behavior of the foam absorbing a part of the impact energy and also reducing the plastic deformation of the skin (force needed to penetrate in the layer), which is convenient for some applications.…”
Section: Introductionmentioning
confidence: 99%
“…Casavola et al [22] studied the low impact behavior of three-layer materials produced by rotational molding made from two polyethylene layers enclosing a foam layer. The results showed that the average force to penetrate the external face was about 28% higher compared to the internal face, which is related to the compression behavior of the foam absorbing a part of the impact energy and also reducing the plastic deformation of the skin (force needed to penetrate in the layer), which is convenient for some applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of research works have been carried out to improve the performance of PE foams such as by adding small amounts of micro or nano particles [12][13][14][15][16] or by sandwiching them in between two rigid polymers [17][18][19]. Such PE foam composites exhibited improved thermal and mechanical behavior [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Sandwich composite structures are made from a single material such as polyethylene (PE) using the rotational molding process, have two solid skins separated by a foam core (Fig. ) . The main advantages of these sandwich structures are high specific stiffness and strength, good bending stiffness, lower weight, excellent thermal insulation and acoustic damping when compared to a solid structure .…”
Section: Introductionmentioning
confidence: 99%